The Impact of Marketing Content and Marketing Influencers on Skincare Product Purchase Decisions through Social Media and Its Implications on Online Customer Reviews - Ade Mayang Putri Rambe; Indra Mawanta Ginting (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine the influence of Marketing Content and Marketing Influencer variables on the purchase decision of skincare products through social media and its implications on online customer reviews. The population in this study is the people of Labuhanbatu Regency. The number of samples in this study was 200 respondents. Statistical testing and data processing are carried out using SmartPLS. The results of the study showed that 1) There was a positive and significant influence between the marketing content variable (X1) on the purchase decision (Y) of skincare products through social media. 2) There was a positive and significant influence between the marketing influencer variable (X2) on the purchase decision (Y) of skincare products through social media. 3) There is a positive and significant influence between the variables of Purchase Decision (Y) on online customer reviews (Z) of skincare products through social media.